The entrepreneurial versus managerial : an empirically based gender study of Singapore woman. - Loh, Sow Wai. (2008)
The rapid economic growth and industrialization of Singapore has created more jobs opportunities for women. 14% of women in the labour force today are in executive or higher position as compared to 8% in 1989. The entrepreneurship rate in Singapore amongst women has risen from 5.3% in 1980 to more than 7% in 1999. (Singapore Labour Force Survey, Ministry of Labour, 1999). This trend is expected to continue due to the increasing aspirations of today's women and as a result of future societal and economic demands. This study explores the characteristics of women entrepreneurs and women managers in Singapore in terms of their interpersonal styles, management styles and personalities. It also looks at their personal backgrounds and life experiences and the relationship of their personal backgrounds and life experiences with the different styles they adopt.